Difficulties with Fine Motor Skills and Cognitive Impairment in an Elderly Population: The Progetto Veneto Anziani. Issue 2 (11th January 2018) - Curreri, Chiara; Trevisan, Caterina; Carrer, Pamela; Facchini, Silvia; Giantin, Valter; Maggi, Stefania; Noale, Marianna; De Rui, Marina; Perissinotto, Egle; Zambon, Sabina; Crepaldi, Gaetano; Manzato, Enzo; et al.
Abstract : Objectives: To investigate dysfunction in fine motor skills in a cohort of older Italian adults, identifying their prevalence and usefulness as indicators and predictors of cognitive impairment. Design: Population‐based longitudinal study with mean follow‐up of 4.4 years. Setting: Community. Participants: Older men and women enrolled in the Progetto Veneto Anziani (Pro.V.A.) (N = 2, 361); 1, 243 subjects who were cognitively intact at baseline were selected for longitudinal analyses. Measurements: Fine motor skills were assessed by measuring the time needed to successfully complete two functional tasks: putting on a shirt and a manual dexterity task. Cognitive impairment was defined as a Mini‐Mental State Examination (MMSE) score less than 24. Results: On simple correlation, baseline MMSE score was significantly associated with the manual dexterity task (correlation coefficient ( r ) = −0.25, P < .001) and time needed to put on a shirt ( r = −0.29, P < .001). Over the study period, changes in time needed to perform the fine motor tasks were significantly associated with changes in MMSE (putting on a shirt: β = 0.083, P = .003; manual dexterity task: β = 0.098, P < .001). Logistic regression analyses confirmed that worse results on tasks were associated with cognitive impairment at baseline (odds ratio (OR) = 2.47, 95% confidence interval (CI) = 1.74–3.50, for the fourth quartile of time needed to put on a shirt; OR = 1.98, 95% CI = 1.42–2.76, for the fourth manual dexterity task quartile) and greater risk of cognitive impairment developing during follow‐up (OR = 4.38, 95% CI = 2.46–7.80, for the fourth quartile of time needed to put on a shirt; OR = 2.20, 95% CI = 1.30–3.72, for the fourth manual dexterity task quartile). Conclusions: Difficulties with fine motor skills are common in older adults, and assessing them may help to identify early signs of dementia, subjects at high risk to develop cognitive decline, and individuals who can be referred to specialists.